Identifikasi Patah Tulang Tangan Manusia dengan Menerapkan Metode Hue Saturation Value (HSV) - Giovani, Hendra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
In identifying broken bone integrity, generally due to trauma. One of the methods used to identify fractures is to look at the picture of the fracture through X-rays or X-rays. Then, it is analyzed manually by a Radiologist. Radiologists often have difficulty in reading X-rays, the presence of faults that cannot be seen by the naked eye and the image quality that contains a lot of noise. And accompanied by the condition of the Radiologist's eyes that are tired after seeing a lot of X-ray images of bones can produce a high level of subjectivity. The level of subjectivity that is meant is the level of differences in observations on X-ray images. For this reason, an approach is needed that can assist radiologists in identifying the location of fractures. This study identifies the ribs of the human hand using the HSV (Hue Saturation Value) method with the aim of classifying the color contrast segmentation that is closest to the way the human eye works and combining information, both color and grayscale (digital images that only have one channel value in each pixel), in other words the value of the RGB portion of an image of a hand fracture